You are on page 1of 3

Coordinate Geometry:

y=mx+c m =gradient c =y intercept

Gradients:
Infinite gradient (x=n) Positive gradient No gradient (x=0, y=infinite) Negative gradient y

Finding the gradient:


y

A = (x,y) B = (x,y)
y x

y B x

Gradient = Note that

also = gradient

FSMQ Maths 2011-2012 Hattie

Finding the perpendicular line: y=mx+c (you are trying to find the perpendicular gradient to this)

If m is called m so the perpendicular line will be called m for clarity. Lets say the gradient of a line is -2 and we are trying to find the perpendicular line. The rule is that m, m = -1 (for instance the perpendicular line to 1 is -1)

Therefore the gradient of the perpendicular line to -2 = (-2m = -1) Here all Ive done is substitute
in the -2 for the m

Rearranged this is (m =

), which equals or 0.5

(the signs cancel out!)

Finding the distance between two points: To find the distance between two points, you can use the Pythagoras theorem. (a+b=c) A = (x, x) and B = (y, y) Therefore this means that AB = (x-x) + (y-y) (if points A and B are on either end of the hypotenuse).

Finding the midpoint of a line between two points: Lets say that on either end of a line the points are A (4, 2) and B (6, 10) The equation used to find the each part of the midpoint is ( Therefore we would work the answer out like this: (6+4)/2 = 5, (2+10)/2 = 6 giving an answer of (5, 6) ).

FSMQ Maths 2011-2012 Hattie

Finding the equation of a straight line: When there is a known gradient and one point Use the equation y-y = m(x-x) This is best explained with an example: Find the equation of the line with gradient 3 which passes through (2, 5) in the form y=mx+c. y-5 = 3(x-2) so y-5 = 3x-6 so y = 3x -1

In the form of px + qy + r = 0

this is 3x + y -1 = 0

When you there are two known points but no known gradient Use the equations y-y = m(x-x) and m =

(the order of the ys and xs can be reversed as long as they are both changed)

This is also best explained with an example: Find the equation passing through (-2, 6) and (4, -6) in the form y=mx+c. y-6 = (x- -2)

so y-6 = 12/-6 (x- -2) so y-6 = -2(x- -2) so y-6 = -2x 4 so y = -2x + 2

In the form px + qy + r = 0

this is -2x + y + 2 = 0

FSMQ Maths 2011-2012 Hattie